ADVANTAGE OF METHYLDIETHANOLAMINE COMPARISON WITH OTHER AMINE IN REMOVAL FROM ACID GASES FROM NATURAL GAS COMPLEXES (Eureka Journal of Physical and Chemical Research, 2026)
Year by years’ number of world's population increasing, so grows the demand for energy. Natural gas is one of important energy resource. It uses not only generation power of energy, but need for produce chemical polymers for example polyethylene and polypropylenes. However, the presence of contaminants in the natural gas, such as H2S and CO2, is the cause of several operational and technical issues ranging from equipment corrosion, fouling, catalyst deactivation, and environmental pollution. Therefore, it is necessary to remove contaminants from these gaseous mixtures for their efficient and safe use in multiple applications. The objective of this review is to explore different methods the acid gas removal (AGR) processes. The choose correctly amine for AGR unit and the main parameters affecting the process have been discussed. In the first part of article, the chemical absorption processes are summarized, including the chemical mechanisms involved and a screening of the main amine-based solvents currently used in such processes. In the second part of article about conditions of chemicals and third part supported by experimental trends of process. Industrial applications of AGR processes have been included in the discussion. Finally, in this direct we indicate why MDEA is benefit choose for AGR system.
Keywords: Amine, acid gas, hydrogen sulfide, carbon dioxide, ucarsol, solvent, absorption, amine regeneration.